668 USEFULNESS OF PRONE-POSITION COMPUTED TOMOGRAPHY AS PREOPERATIVE SIMULATION OF THORACOSCOPIC ESOPHAGECTOMY FOR THORACIC ESOPHAGEAL CANCER. (17th September 2021) - Higuchi, Tadashi; Koyanagi, Kazuo; Ninomiya, Yamato; Yatabe, Kentaro; Yamamoto, Miho; Tajima, Kohei; Ozawa, Soji
Abstract:  : The study aimed to evaluate the usefulness of prone-position computed tomography (CT) for predicting relevant thoracic procedure outcomes in minimally invasive esophagectomy (MIE) for thoracic esophageal cancer. Methods: A total of 59 patients underwent esophagectomy between May 2019 and December 2020 in Tokai University Hospital. Preoperative CT imaging was conducted with the patient in both the supine and prone positions, and the magnitude of change in the intramediastinal space was calculated. In the 56 patients (94.9%) who had undergone MIE, the effects of such a difference on the surgical outcomes were analyzed. Results: A significant correlation of the magnitude of change in VE (distance between ventral aspect of vertebral body and the midpoint of esophagus) with the surgical outcome was revealed in the 17 patients (30.4%) in whom the magnitude of change in VE was over the 75th percentile. That is, in this subgroup, VE showed a negative correlation with the thoracic operation time (p = 0.01) and blood loss during the thoracic procedure (p = 0.01). Multivariate analysis identified a magnitude of change in VE □9 mm as an independent risk factor for postoperative pneumonia. Conclusion: This study indicates that preoperative prone-position CT imaging is useful for predicting the level of ease or difficulty of securing an adequate operative field, surgical outcomes, and the risk of postoperative pneumonia in MIE.